Anterior uveal and episcleral metastases from carcinoma of the breast - Reddy, S.C.; Madhavan, M.; Mutum, S.S. (S. Karger, 2000)
Breast carcinoma is the most common primary tumor producing intraocular metastasis. Metastases to the iris and ciliary body are relatively rare. The authors report a case of a 61-year-old lady, operated for carcinoma of the left breast 3 years back, who presented with symptoms and signs of acute narrow-angle glaucoma in the right eye. A diffuse whitish plaque-like mass in the upper nasal quadrant of the iris with an episcleral nodule on the limbus in the corresponding area and all the signs of acute narrow-angle glaucoma were present in the right eye. Intraocular pressure was controlled medically. Fine-needle aspiration cytology from the episcleral nodule showed malignant cells. Histopathology of the excised nodule showed metastatic poorly differentiated carcinoma, and the cellular pattern was similar to the carcinoma of the breast. There was no other metastasis anywhere in the body. Fine-needle aspiration cytology from an external lesion of the eye is a less invasive and easier procedure than paracentesis to diagnose the metastatic nature of the lesions. The rare features in our case are the clinical presentation as acute glaucoma and the ocular structures being the first and only site of metastasis. Copyright (C) 2000 S. Karger AG, Basel.